COMPETITIVENESS OF THE AGRI-FOOD SECTOR OF THE REPUBLIC OF SERBIA - Dimitrijević, Miloš S (Journal of Agricultural Sciences (Belgrade), 2023)
The competitiveness of the agri-food products is among the key factors in encouraging exports and economic development, especially for developing countries. Competitiveness can be influenced by increasing productivity, applying modern knowledge, technologies, innovating processing capacities and producing a high-quality final product with high value added. Agriculture of Serbia is very important for economic growth. The subject of the paper is to examine the most important export agri-food products of Serbia, as well as the most important markets for their exports. Using the RCA and ARCA indexes, the comparative advantages of these products in trade were examined, which is the goal of the research, and then, with multiple regression, the impact on exports. Although significant agri-food products achieve comparative advantages, the decline in their competitiveness has a negative impact on exports. That is why it is necessary to invest in modern equipment, develop innovative approaches, such as organic production and introduction of innovations in order to improve quality standards and differentiation of products, as important prerequisites for improving competitiveness and encouraging exports of the agri-food sector.
Keywords: competitiveness; agri-food sector; RCA; ARCA